Manejo de açaizais nativos e sustentabilidade: realidade multidimensional de agroecossistemas familiares na comunidade Mamangal Grande, Igarapé-Miri (PA). - SILVA, Tayse Fernanda do Amaral (Instituto Federal de Educação, Ciência e Tecnologia do Pará, 2023)
The county of Igarapé-Miri, located in the Baixo Tocantins region, is one of the main producers of acai (Euterpe oleraceae Mart.) of the region, and in the midst of this fact, it is observed that over the years, with the extraction of the fruit, there was a change in the local landscape, expressing itself in a reduction of species diversity and prioritization of only one species during management. Considering that the reduction of species diversity, linked to the intensification of the management of açaí, can be configured in environmental and social risks, compromising the sustainability of family agroecosystems, the objective of the study is to analyze the strategies and impacts of family floodplain agroecosystems, keeping açaí as the main productive strategy, of which, it has as specific objectives: a) to characterize local management of native açaizal and their respective production systems (agroecosystems); a) compose a set of multidimensional indicators, referenced by the local agro-ecosystems; c) assess the state of sustainability of the family's lowland agro-ecosystems, with açaí as a strong component. The research was carried out in the Mamangal Grande community and was divided into three stages. The first consisted of a bibliographic and exploratory survey on the use of indicators in lowland agroecosystems. The second stage focused on building indicators with the community. Lastly, in the third, the indicators constructed to evaluate the agroecosystems of the riverside were used. As a result, it was noted that most of the indicators used are adaptations of reference works, but that they underwent some modification in their structure, due to local characteristics. As for the indicators constructed, a total of 22 indicators were added, of which 21 were simple and 1 composed. In the general assessment of the sustainability status of the Mamangal Grande community, the agroecosystems that showed the greatest diversity of productive activities and had a closer relationship with social organizations, obtained the best performances in the evaluation of the indicators. When doing an analysis of family agroecosystems, it is noticed that each riverside shows a diversified and complex way of survival. The seasonality of açaí income ends up becoming the main problem for families, especially for those who have this activity as the only source of income, because during the off-season, financial resources become scarce, compromising the means of social reproduction.